Effect of loading spectrum with different single pulsing time on the cyclic ablation of C/C-SiC-ZrB2-ZrC composites in plasma. (November 2021) - Liu, Lei; Li, Boyan; Feng, Wei; Tang, Chengwei; Zhang, Jiaping; Yao, Xiyuan; Yang, Zhong; Guo, Yongchun; Wang, Ping; Zhang, Yang
Abstract: To support the application for piston of advanced internal combustion engine and pantograph slide plate of high-speed rail, cyclic ablation with different loading spectrums in alternate plasma combustion and compressed air flow were performed by adjusting single impacting time to understand the characteristics of C/C-SiC-ZrB2 -ZrC composites in high frequent pulsing fluid at ultra-high temperature. When the loading time increased from 0.5 to 5 s, the ablation rates rose sharply while the surface temperature changed incrementally. Ablation morphology indicated that the change of dominant ablation mechanism from mechanical erosion to chemical reaction resulted in the sharp rise of the ablation rates. Highlights: C/C-SiC-ZrB2 -ZrC were ablated according to different loading spectrums. Ablation rates were much lower under 0.5 s single impacting than these under 5 s. Mechanical erosion dominated the high frequent pulsing cyclic ablation.